Kolaborasi Guru PAI Dan Orang Tua Dalam Pembentukan Akhlak Siswa SMP Aisyiyah Talang Rimbo Baru - Mirzon Daheri; Aniza; Anisa Aspira; Candra; Ari Nandi Kuncoro (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
The purpose of this study is to describe and analyze the role of Islamic Religious Education teachers in shaping the akhlakul karimah students of Aisyiyah Middle School Creative School. Describe and analyze the role of parents in shaping the akhlakul karimah students of the Aisyiyah Middle School Creative School. Describe and analyze the collaboration of parents and teachers of Islamic Religious Education in forming akhlakul karimah students at Aisyiyah Middle School Creative School. This type of research is field research (field research) which is descriptive in nature. To obtain research data, data collection techniques were carried out, where the technique had three stages, namely observation, interviews, and documentation. The data analysis techniques used are Data Reduction, Data Analysis, and Data Verification. The conclusion of this study is the Collaboration of PAI Teachers and Parents in the Formation of Student Morals at Aisiyyah Creative Middle School, namely by providing understanding in the form of motivational values ​​about good morals to students, controlling or supervising all student activities including in implementing good morals, and providing punishment for students who commit disgraceful acts.